Inhibition of intraocular fibrin formation with annexin V. Issue 8 (August 1992) - Chollet, P; Malecaze, F; Hullin, F; Raynal, P; Arne, J L; Pagot, V; Ragab-Thomas, J; Chap, H
Abstract : Annexin V is a member of the calcium- and phospholipid-binding proteins, known to have an antithrombotic effect. For the first time, we have tested its ability to prevent intraocular postoperative fibrin formation in a standardised rabbit model and compared its effect with that of heparin. Annexin V, 20 micrograms and 60 micrograms, injected in the anterior chamber post-operatively, significantly reduced the area of the fibrin clot and its time to clearing. Annexin V appeared to be as efficient as heparin. It probably acts by preventing phospholipids from playing their role in the coagulation cascade which leads to fibrin formation. Furthermore, annexin V has an anti-inflammatory effect by protecting phospholipids from phospholipase A2 activity. Therefore, annexin V might be considered as a new therapeutic agent acting both on fibrin formation and inflammatory processes.